Charcot‐Marie‐Tooth disease‐associated mutants of GDAP1 dissociate its roles in peroxisomal and mitochondrial fission. (30th April 2013) - Huber, Nina; Guimaraes, Sofia; Schrader, Michael; Suter, Ueli; Niemann, Axel
Abstract : Mitochondria and peroxisomes can be fragmented by the process of fission. The fission machineries of both organelles share a set of proteins. GDAP1 is a tail‐anchored protein of mitochondria and induces mitochondrial fragmentation. Mutations in GDAP1 lead to Charcot‐Marie‐Tooth disease (CMT), an inherited peripheral neuropathy, and affect mitochondrial dynamics. Here, we show that GDAP1 is also targeted to peroxisomes mediated by the import receptor Pex19. Knockdown of GDAP1 leads to peroxisomal elongation that can be rescued by re‐expressing GDAP1 and by missense mutated forms found in CMT patients. GDAP1‐induced peroxisomal fission is dependent on the integrity of its hydrophobic domain 1, and on Drp1 and Mff, as is mitochondrial fission. Thus, GDAP1 regulates mitochondrial and peroxisomal fission by a similar mechanism. However, our results reveal also a more critical role of the amino‐terminal GDAP1 domains, carrying most CMT‐causing mutations, in the regulation of mitochondrial compared to peroxisomal fission. Charcot‐Marie‐Tooth disease‐associated mutants of GDAP1 dissociate its roles in peroxisomal and mitochondrial fission: It is shown that, in addition to its role at mitochondria, the tail‐anchored protein GDAP1 also regulates fission events at peroxisomes. Intriguingly, mutants of GDAP1 associated with inherited peripheral neuropathies differently affect peroxisomal and mitochondrial fission.